Numerical study of the intensification of single-phase heat transfer in a sandwich-like channel using staggered miniature-pin fins - Gemici, Zafer; Budakli, Mete (TAYLOR & FRANCIS INC, 2024)
This study presents the numerical analysis of single-phase forced convection heat transfer and pressure drop during internal flow in a shallow, rectangular sandwich-like copper channel heated from both the top and the bottom. Simulations were conducted using a commercial finite volume solver that solves governing continuity, momentum, and energy equations simultaneously. The bottom side of the channel was considered with arrays of rectangular miniature-pin fins. The miniature-pin fin geometry was modeled in a staggered configuration with tip clearance from the opposite surface while the orientation of the fins was directed parallel to the flow direction of the working fluid. Water was used as a working fluid with a fully developed velocity profile at the channel entry. Simulations were carried out for varying inlet temperatures and mass flow rates. All calculations were performed with the RNG k-epsilon model to model complex turbulent flows appropriately. Grid independence and validation analyses were also conducted. With the validated model, additional analyses were performed for 0, 0.1, 0.3, 0.6, and 1 mm tip clearances, and correlations were proposed after performing regression analyses for the friction factor and heat transfer coefficient. The calculations revealed that in contrast to a straight (nonfinned) surface, up to 220% larger heat transfer coefficients could be obtained for the finned surfaces under comparable operating conditions. It was also shown that tip clearance in turbulent flow affects heat transfer negatively. With increasing clearance, the Nusselt number decreased; in other words, heat transfer worsened. On the other hand, the use of miniature-pin fins led to a rise in the pressure drop over the entire heated length. For the Reynolds number spectrum of 4000-20000, the ratio of the friction coefficient of the finned surface to the friction coefficient of the nonfinned surface varied from 6 to 5 while with a further reduction in pressure loss a value of approximately 4 could be obtained for larger tip clearances. Hence, with larger tip clearances, the friction factor decreased, reflecting the abatement of pressure loss.
Keywords: Forced convection; miniature-pin fin; rectangular narrow channel; single-phase flow; tip clearance; THERMAL MANAGEMENT-SYSTEM; FRICTION FACTOR; FLUID-FLOW; PERFORMANCE ANALYSIS; TURBULENT-FLOW; PRESSURE-DROP; OPTIMIZATION; BATTERY; ARRAYS; Thermodynamics; Mechanics